Convenient synthesis of enantiomerically pure (R)-mexiletine using hydrolytic kinetic resolution method - Sasikumar, Murugesan; Nikalje, Milind D.; Muthukrishnan, Murugan (Tetrahedron-Asymmetry, 2009)
Enantiopure (R)-mexiletine was prepared in a simple and practical way using hydrolytic kinetic resolution method of terminal epoxide by Jacobsen catalyst. High enantiomeric purity (98% ee) was achieved and the method is well amenable to industrial scale-up. (C) 2009 Elsevier Ltd. All rights reserved.

Facile enantioselective synthesis of enantiomerically pure (R)-phenoxybenzamine hydrochloride using the hydrolytic kinetic resolution method - Nikalje, Milind D.; Sasikumar, Murugesan; Muthukrishnan, Murugan (Tetrahedron-Asymmetry, 2010)
A practical and highly efficient enantioselective synthesis of (R)-phenoxybenzamine hydrochloride has been described for the first time using Jacobsen's hydrolytic kinetic resolution of a terminal epoxide as a key step and source of chirality. (C) 2010 Elsevier Ltd. All rights reserved.

New enantioselective synthesis of the anti-parkinson agent safinamide - Reddi, Anjaneyulu; Mujahid, Mohammad; Sasikumar, Murugesan; Muthukrishnan, Murugan (Synthesis-Stuttgart, 2014)
An alternative highly enantioselective synthesis of the anti-Parkinson agent safinamide from simple, commercially available, starting materials is described. The protocol might also be useful in the synthesis of structural variants of safinamide, such as ralfinamide or related analogues
Keywords: Amides; medicinal chemistry; safinamide; stereoselective synthesis

Efficient synthesis of the opioid analgesic (R)-phenampromide via an aziridinium ion - Mujahid, Mohammad; Mujumdar, Prashant; Sasikumar, Murugesan; Deshmukh, Shirish P.; Muthukrishnan, Murugan (Tetrahedron-Asymmetry, 2017)
A simple and efficient synthesis of the opioid analgesic agent (R)-phenampromide with high enantiopurity (> 99% ee) via the formation of an aziridinium ion as a key step using commercially available starting material is described. (C) 2017 Elsevier Ltd. All rights reserved.

New and efficient enantioselective synthesis of both enantiomers of the calcium channel blocker bepridil - Mujahid, Mohammad; Subramanian, Jambu; Nalla, Viswanadh; Sasikumar, Murugesan; Kunte, Sunita Sharad; Muthukrishnan, Murugan (New Journal of Chemistry, 2017)
A concise and efficient enantioselective synthesis of both enantiomers of bepridil, a calcium channel blocker, is reported. Jacobsen's hydrolytic kinetic resolution method was utilized to resolve racemic 2-(isobutoxymethyl) oxirane. The incorporation of the succinimide moiety by the Mitsunobu reaction, which was investigated in detail, occurred without any loss of enantioselectivity. Using this strategy, both enantiomers of the target molecule were obtained in good yield and with high enantiopurity (ee > 99%).

Efficient synthesis of optically active herbicide (S)-metolachlor via reductive ring opening of 2-methoxymethylaziridine - Nalla, Viswanadh; Mujahid, Mohammad; Sasikumar, Murugesan; Mujumdar, Prashant; Muthukrishnan, Murugan (Arkivoc, 2023)
An efficient synthesis of a well known chiral herbicide, (S)-metolachlor has been described using 2methoxymethylaziridine ring formation and reductive ring opening as key steps using commercially available (R)-epichlorohydrin. The present protocol delivers the required enantiomer of metolachlor in overall yield of 50.8% and high enantiopurity (>99%).
Keywords: Aziridine; Epoxide; Epoxide ring opening; herbicide synthesis; Metolachlor